the problematic between classical and vernacular Arabic dialects at al-Tayeb Al-Bakoush (Damascus University Journal of arts and humanities sciences, 2025)
Modern linguistics is concerned with the interrelationship between the local language and the local dialect, so Al-Bakush called for the study of the vernacular and modern dialects explicitly, stressing their importance in studying the language, and his most important position on the history of the development of the language.This research attempts to shed light on his study to discuss the problematic between classical and vernacular dialects in the book (From the Issues of the Contemporary Arabic Language), considering that each of them is a language in its own right. Perhaps what is meant by his posing of this problem is to study the slangdialects as a And if it is not read, far from chaos, a language of its own is complementary to the picture of linguistic development. On this basis, al-Bakoush studied the classical language and the vernacular dialect language with rules and laws.
Keywords: Classical Arabic; Colloquial Dialects; Rules; Melody